A arquitetônica do ato de ilustrar de Rui de Oliveira contribuições dos livros de imagem para a formação do pequeno leitor literário - Cabral, Gisele de Assis Carvalho (Editora Oficina Universitária, 2022)
Rui de Oliveira's Architectonics of the Act of Illustrating: Contributions of Picture Books to the Formation of Little Literary Readers is a book that reveals content that is both poetic and scientific. Fruit of a Master's dissertation, it shows us what Gisele de Assis Carvalho Cabral, its author, considered it a priority to share with her readers: the essentiality of reading Children's Literature books for the formation of the child and, specifically, the role of illustrations in the formation process of the little reader. Among all the illustrators and producers of stories told through images or combining words and images, Gisele chose Rui de Oliveira who, in more than forty years of work with the art of illustrating stories, developed what they call an "approach method" or " plastic solutions" to think about each work in its uniqueness, always concerned with meeting the needs of appropriating artistic, aesthetic, essentially humanizing values on the part of children. Rui de Oliveira's artistic production reveals that the picture book translates its author's worldview, the way he thinks and the way in which he describes objects, places, people and their physical and psychological characteristics, their emotions, and narrates the facts, the events experienced by the characters, in constant dialogue with the reader who, in response to the questions posed by the author, looks inside himself, considers and elaborates everything perceived, understood and felt, broadening his look beyond appearances, discovering a world hitherto unknown, although he was involved in it all the time. The author demonstrates that the other, with his way of expressing words and images, sharpens the reader's curiosity, imagination and creativity and offers him opportunities to penetrate the world of culture, aesthetics, art, philosophy... in short, in an immense world of possibilities that unfolds before your eyes! To check!